2001
DOI: 10.1159/000049529
|View full text |Cite
|
Sign up to set email alerts
|

TU-572, a Potent and Selective CD45 Inhibitor, Suppresses IgE-Mediated Anaphylaxis and Murine Contact Hypersensitivity Reactions

Abstract: Background: CD45, receptor-type protein tyrosine phosphatases (PTPases) are essential components of signaling through both the T cell receptor and the B cell antigen receptor. However, the functional significance of CD45 in the signaling pathway through the high-affinity immunoglobulin (Ig) E receptor has not yet been established. In this study, we demonstrate that the potent CD45 inhibitor negatively regulates IgE-dependent anaphylaxis and contact hypersensitivity reactions. Method: We have previously found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Antibodies directed to the extracellular domain of CD45 have been used for cancer management (Hamaguchi et al, 2001;Nemecek and Matthews, 2002;Pagel et al, 2003). One problem with the use of anti-CD45 mAbs is that these agents target all cells expressing CD45 (normal resting and rapidly proliferating lymphoid cells), regardless of whether CD45 is functionally essential to that cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies directed to the extracellular domain of CD45 have been used for cancer management (Hamaguchi et al, 2001;Nemecek and Matthews, 2002;Pagel et al, 2003). One problem with the use of anti-CD45 mAbs is that these agents target all cells expressing CD45 (normal resting and rapidly proliferating lymphoid cells), regardless of whether CD45 is functionally essential to that cell.…”
Section: Discussionmentioning
confidence: 99%
“…To control the growth of leukemias and lymphomas, antibodies directed to the extracellular domain of CD45 have been used to eliminate CD45 1 cells but have had limited clinical efficacy (Hamaguchi et al, 2001;Nemecek and Matthews, 2002;Pagel et al, 2003). One problem is that anti-CD45 monoclonal antibodies (mAb) target all CD45 1 cells, regardless of whether CD45 activity is functionally essential to that cell.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive CD45 inhibitors that block substrates from docking (Beers et al, 1997) and substrate analogs that poison the catalytic pocket have been reported (Urbanek et al, 2001), with an in vitro IC 50 value of approximately 0.2 mM and activity in antiproliferative assays. One competitive inhibitor (a benzimidazole derivative) had effects on histamine release from rat peritoneal mast cells (Hamaguchi et al, 2001). Unfortunately, these CD45 inhibitors are not clinically useful.…”
Section: Introductionmentioning
confidence: 99%
“…Protein phosphatase inhibitors are useful tools to reveal signal transduction pathways of immune response as well as to cure immunological diseases [27,28]. In this report, we identified 4‐iA as a potent VHR inhibitor and investigated the effect of 4‐iA on VHR, a well‐characterized member of DSPases.…”
Section: Discussionmentioning
confidence: 99%